Factor Affecting Job Satisfaction in Community Pharmacists: A Review - Sintaresmi Kusumah Wardani; Susi Ari Kristina; Nanang Munif Yasin (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Job satisfaction, especially pharmacists', must be considered, as their work is related to patient safety. This review aims to identify job satisfaction, the factors that influence it, and the instruments used to measure it in community pharmacists. This systematic review used the PRISMA methodology and was conducted in December 2022 using three search engines (PubMed, Science Direct, and Google Scholar) by retrieving articles published in the last ten years. Two researchers independently assess the quality of articles using JBI Critical Appraisal. The keywords "Job Satisfaction" and "Community Pharmacist" were used to search articles and 360 articles were obtained. In this review, only eight articles met the criteria. The inclusion criteria include cross-sectional studies, publication in English between 2012 and 2022, and research topics on the job satisfaction of community pharmacists. This systematic review excludes duplicate articles and no full text and is included in pilot projects, reviews, letters, or comments. Three articles from Lithuania, the US, and Sweden reported high levels of job satisfaction; five articles from Iraq, Jordan, Malaysia, and Ethiopia reported moderate to low levels. Only one study did not report job satisfaction levels. The results showed that community pharmacists have low to high job satisfaction with several influencing factors, namely demographic factors (gender, age, working hours), intrinsic (recognition), and extrinsic (income). The limitation of this study is the number of articles included, there are differences in the identification of influence factors, and the studies are only quantitative.